2022
DOI: 10.3390/foods11020191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Flavor Precursors and Flavor Fingerprints in Grazing Lambs by Foodomics

Abstract: Tan sheep are greatly preferred by consumers in China because of their nutritional value and unique flavor. However, the meat quality of Tan sheep has decreased due to the change in feeding systems from grazing to indoor. Studies investigating the mechanisms for the decrease in meat quality are limited. A total of 28 Tan sheep were randomly allocated to two treatments, receiving a concentrated diet, or pasture. Flavor precursors and volatile compounds were analyzed with foodomics. E-nose and E-tongue analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Aldehydes, alcohols, and ketones were the most abundant volatiles in all samples, accounting for more than 70% of the total volatiles detected. It has been observed that these compounds show a higher relative abundance in lamb meat regardless of if the animals are reared on pastures or fed concentrates indoor [ 27 ]. Aldehydes and ketones were found in greater amounts ( p < 0.05) in the ALGCON treatment ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldehydes, alcohols, and ketones were the most abundant volatiles in all samples, accounting for more than 70% of the total volatiles detected. It has been observed that these compounds show a higher relative abundance in lamb meat regardless of if the animals are reared on pastures or fed concentrates indoor [ 27 ]. Aldehydes and ketones were found in greater amounts ( p < 0.05) in the ALGCON treatment ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to our results, ethanol has been reported in a higher amount in meat from pasture-fed lambs as well as in beef cattle fed 100 mg/d of Schizochytrium sp. powder, i.e., from animals with intramuscular fat rich in long chain omega-3 FA [ 27 , 36 ]. The γ-dodecalactone has been reported in greater amounts in loin fat of a clover-finished lamb than in that of a maize-finished lamb [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The e-tongue can be used for rapid, accurate, qualitative and quantitative analyses of flavors [ 9 ]. Yuan et al [ 10 ] analyzed the diferences of aroma and taste of Tan sheep using an e-nose and e-tongue. Chromatographic techniques such as gas chromatography-mass spectrometry (GC-MS) and gas chromatography-ion mobility spectrometry (GC-IMS) are currently important research tools for analyzing food flavor [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies concerning the volatile compound composition in meat, multivariate statistical techniques have been applied for data processing. Therefore, PCA for data visualization has been used to study the impact of different forage systems on the volatile composition of commercial lambs [16,17]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ref. [17] investigated the overall aroma profile in grazing lambs. According to the PCA results, the first two principal components explained 94.1% of the variance in aroma.…”
Section: Introductionmentioning
confidence: 99%